2008
DOI: 10.1128/iai.00897-07
|View full text |Cite
|
Sign up to set email alerts
|

Both Decorin-Binding Proteins A and B Are Critical for the Overall Virulence of Borrelia burgdorferi

Abstract: The lack of dbpA alone precluded the pathogen from colonizing the heart tissue, and B. burgdorferi deficient for DbpB was recovered only from 42% of the heart specimens of infected mice. Although B. burgdorferi lacking either dbpA or dbpB was consistently grown from joint specimens of almost all infected mice, it generated bacterial loads significantly lower than the control. The deficiency in either DbpA or DbpB did not reduce the bacterial load in skin, but lack of both significantly did. Taken together, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 40 publications
6
135
3
3
Order By: Relevance
“…Similarly, Mn, possibly via the Mn-dependent Fur homolog BosR (23,33,37,38) Our study has demonstrated that the Lyme disease spirochete requires BmtA's Mn-associated transport function(s) to maintain its infectious cycle in nature. To date, only relatively few virulence factors, including OspC, DbpB/A, OspA/B, PncA, and BptA, have been identified in Bb, and the functions of most of these proteins remain obscure (4,5,(7)(8)(9)(10). In this regard, our identification of BmtA as a novel virulence factor in Bb provides further insights into molecular mechanisms that contribute to Bb's survival in nature and may lead to new strategies to interrupt the spirochete life cycle.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Mn, possibly via the Mn-dependent Fur homolog BosR (23,33,37,38) Our study has demonstrated that the Lyme disease spirochete requires BmtA's Mn-associated transport function(s) to maintain its infectious cycle in nature. To date, only relatively few virulence factors, including OspC, DbpB/A, OspA/B, PncA, and BptA, have been identified in Bb, and the functions of most of these proteins remain obscure (4,5,(7)(8)(9)(10). In this regard, our identification of BmtA as a novel virulence factor in Bb provides further insights into molecular mechanisms that contribute to Bb's survival in nature and may lead to new strategies to interrupt the spirochete life cycle.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, extensive efforts have been directed toward elucidating the mechanisms by which Bb cycles, adapts, and sustains itself in these diverse niches. It is now well established that outer surface (lipo)protein C (OspC), OspA/B, decorin-binding protein B/A (DbpB/A), PncA, and BptA are required by Bb for efficient infection of ticks or mammalian hosts (4)(5)(6)(7)(8)(9)(10). It is also generally accepted that the recently discovered Rrp2-RpoN ( 54 )-RpoS ( S ) regulatory pathway plays prominently in Bb's virulence expression (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Although a majority (59/98) of genes in this category encode hypothetical proteins and conserved hypothetical (Caimano et al, 2004;Hagman et al, 1998;Shi et al, 2008). In addition, eight genes encoding proteins related to chemotaxis were found to be induced by Rrp2, RpoN and RpoS.…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
“…Several plasmids, such as lp25, lp28-1 and lp36, are essential for borrelial infectivity (Jewett et al, 2007;Purser & Norris, 2000;Stewart et al, 2005). Plasmid lp54 has been implicated as being important for the survival of B. burgdorferi in both tick and mammalian hosts, largely because of the presence of the ospAB and dbpBA operons (Caimano et al, 2005;Hagman et al, 1998;Neelakanta et al, 2007;Shi et al, 2008;Yang et al, 2004). Many other genes encoded on lp54 have been found to be differentially regulated in response to temperature, pH and other mammalian-derived signals, which are presumed to be mediated, at least in part, by RpoS (Caimano et al, 2005;Clifton et al, 2006;Ojaimi et al, 2003;Revel et al, 2002).…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
See 1 more Smart Citation